2014
DOI: 10.1088/0953-2048/27/6/065018
|View full text |Cite
|
Sign up to set email alerts
|

The effects of co-wound Kapton, stainless steel and copper, in comparison with no insulation, on the time constant and stability of GdBCO pancake coils

Abstract: Recently, studies of partially insulated, high-temperature superconducting (HTS) coils have shown application in the design and construction of compact, stable and self-protecting HTS coils. This article presents the electrical characteristics of HTS coils based on the turn-to-turn inserted materials and conditions. Three partially co-wound pancake coils were fabricated and tested. Each coil was partially co-wound with Kapton, stainless steel and copper tape at every fourth turn of the winding. Tested coils we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 13 publications
(19 reference statements)
0
35
0
Order By: Relevance
“…To date the HTS NI technique has been actively studied, but mostly in small test-coil scales [6][7][8][9][10][11][12][13][14]. In 2012, we experimentally demonstrated the self-protecting feature of a single-pancake REBCO NI coil at 1580 A mm −2 on an 'overcurrent' test run in a bath of liquid helium at 4.2 K [3].…”
Section: Introductionmentioning
confidence: 99%
“…To date the HTS NI technique has been actively studied, but mostly in small test-coil scales [6][7][8][9][10][11][12][13][14]. In 2012, we experimentally demonstrated the self-protecting feature of a single-pancake REBCO NI coil at 1580 A mm −2 on an 'overcurrent' test run in a bath of liquid helium at 4.2 K [3].…”
Section: Introductionmentioning
confidence: 99%
“…There is a novel technique in recent years for the quench protection of HTS magnets. The no-insulation (NI) or metallicinsulation (MI) technique can protect the magnet from a quench event or even an over-current [55]. Raw wire contact between two consecutive turns works as current flow path in radial direction and acts as a resistor in parallel with each pancake.…”
Section: Ni Techniquementioning
confidence: 99%
“…Raw wire contact between two consecutive turns works as current flow path in radial direction and acts as a resistor in parallel with each pancake. Co-winding with metal wire like SS for REBCO wire is more realistic for a fast ramp-down of an HTS magnet than co-winding with copper or NI [55][56][57]. Nickel alloy as the strengthening layer of the Bi2223 wire has comparable electrical resistivity at 4 K to the SS, so NI technique with direct usage of the type HT-NX raw wire in winding as an MI treatment can be an option for the quench protection.…”
Section: Ni Techniquementioning
confidence: 99%
“…However, the introduction of these extra degrees of freedom to the current flow, poses challenges when attempting to model and understand the current and field distribution within an NI coil. Experiments and modelling [15][16][17][18][19][20][21][22][23] have shown that current flow, and the associated electric and magnetic fields are more complicated than that captured by a simple equivalentcircuit model. However, a full resolution model of such NI coils is practically difficult to implement due to the high aspect ratio of the superconductor and the need to consider the currents flowing normal to the conductor's surface.…”
Section: Introductionmentioning
confidence: 99%